RNA accumulation in Candida tropicalis based on cofactor engineering. Issue 3 (3rd April 2019) - Li, Bingbing; Liu, Ying; Wang, Lianzhe; Hong, Jun; Chen, Yong; Ying, Hanjie
ABSTRACT: Redox cofactors play an important role in biosynthetic and catabolic reactions and the transfer of energy for the cell. Therefore, studying the relationship between cofactor perturbation and metabolism is a useful approach to improve the yield of target products. To study RNA accumulation and metabolism when intracellular cofactor balance was impaired, the water-forming NADH oxidase ( NoxE ) from Lactococcus lactis and membrane-bound transhydrogenase ( PntAB ) from Escherichia coli were expressed in Candidatropicalis no. 121, respectively. Expression of noxE significantly decreased the intracellular NADH/NAD + ratio, but the NADPH/NADP + ratio did not differ significantly. PntAB increased the intracellular NADH pool, while the NADPH/NADP + ratio decreased. The perturbation of the cofactors caused a large redistribution of metabolic fluxes. The biomass and RNA content decreased by 11.0% and 10.6% in pAUR-noxE strain, respectively, while the RNA content increased by 5.5% and the biomass showed no signification difference in pAUR-pntAB strain. Expression of noxE and pntAB led to decreases and increases in the ATP concentration and yield of RNA, respectively, which also indicated that ATP plays an important role in the RNA biosynthesis. Abstract : Redox cofactors play an important role in biosynthetic and catabolic reactions and the transfer of energy for the cell